STUDENTS’ PERCEPTIONS OF DIAGNOSTIC TESTS IN ENGLISH LEARNING: A QUALITATIVE CASE STUDY OF AWARENESS GAP IN VOCATIONAL EDUCATION - Sintiya Daud; Andi Nurwati; Alvons Habibie; Harni Jusuf; Adinawati Helingo (JETAL: Journal of English Teaching & Applied Linguistic, 2026)
This study aims to examine the perceptions of vocational high school students regarding diagnostic tests in English language learning, highlighting the limitations of previous studies that have focused solely on pedagogical functions without exploring how students interpret and utilize the test results. This study employs a qualitative approach using a case study design involving 15 tenth-grade students from three departments (Mechanical Engineering, Accounting, and Hospitality) at SMK Negeri 1 Limboto, selected through purposive sampling. Data were collected through semi-structured interviews lasting 10–15 minutes, recorded, and transcribed verbatim, then analyzed using thematic analysis through a systematic coding process. The results indicate that students hold positive perceptions of diagnostic tests, particularly regarding their role in enhancing awareness of English language proficiency and motivating learning. However, the primary finding of this study is the existence of an “awareness gap,” wherein the majority of students do not yet understand how test results are utilized in the learning process. This finding indicates that the effectiveness of diagnostic tests depends not only on their administration but also on students’ engagement in understanding and utilizing test results. Theoretically, this study reinforces the assessment for learning framework by emphasizing the importance of student awareness, while practically, it implies the need for more structured and transparent feedback regarding the use of test results.